(untitled) (International Journal of Environmental Sciences, 2025)
The 15th Finance Commission Report (2020) suggests that India has underperformed in terms of controlling maternal and child mortality and fertility rate. The objective of this paper is to examining health status of North Eastern states of India which comprises of 45.77 million populations (Census, 2011). Among the various indicators as declared by World Health Organization, we have considered three health indicators named infant mortality rate, neonatal mortality rate and under five (5) mortality rate over the period of seven years from 2005-16 to 2020-21. Methodology: the present study is based on secondary data published by various reports of National Family Health Survey and yearly report of National Health Profile. Tabular presentation and multiple bar diagram are used to explain the health status of the states. Lorenz curve and Gini coefficient are used in measuring the inequality in distribution of health positions. Findings: It is observed that except Assam and Meghalaya all other states of the region are able to reach below the national level in controlling infant and neonatal mortality. The hilly states like Sikkim, Manipur, Mizoram and Nagaland has achieved better positions in controlling all the three mortality rates over the year. On the other hand the distribution of health facilities are more heterogeneous among states that has shown by the moderate Gini value (0.426) and deviations of Lorenz curve from the line of equality. It has been observed that though the health status indicators are poor in Assam, Meghalaya and Tripura but all of them are able to improve their positions.